The leader lab : core skills to become a great manager faster - Luna, Tania; Renninger, LeeAnn (Ascent Audio, 2021)
What if you could become a great manager, leader, and communicator faster? The Leader Lab is a high-speed leadership intensive, equipping managers with the Swiss Army Knife of skills that help you handle the toughest situations that come your way. Through painstaking research and training over 200,000 managers, authors Tania Luna and LeeAnn Renninger, PhD (co-CEOs of LifeLabs Learning) identified the most important skills that distinguish great managers from average. Most importantly, they've discovered how to help people rapidly develop these core skills. The result? You quickly achieve extraordinary team performance and a culture of engagement, fulfillment, and belonging. Too often, folks are promoted without any training for the countless crucial responsibilities of the modern manager. The Leader Lab serves as your definitive guide to what it means to be a great manager today-and how to become a great leader faster. This book is based on LifeLabs Learning's wildly successful workshop series. It combines research, tools, and the playful, fluff-free style that's made LifeLabs the go-to professional development resource for over 1,000 innovative companies around the world.